EPISODIC ISSUES «IN THE LIFE OF ST. DAVID GAREJELI» - Mikhaeil Khutsishvili; Miranda Todua (Arts Academy)
One episode of «the life of Saint David Garejeli» is discussed in the work, in which it is narrated how Saint David Garejeli (6th century) converted to Christ an unrighteous man named Bubakr, who threatened to kill David, but after a miracle performed by David, he turned to Christ. From the work, we can see that David speaks to Bubakr in Armenian, which indicates that Bubakr is Armenian. But the author only hints about the Armenianness of this person and does not say it directly. In the present work, the attention is focused on the fact that in the Middle Ages the word `Armenian', along with the ethnic one, also had a confessional meaning and that it was also used in the meaning of Monophysite. The authors of the article express the opinion that in the previous text, which the creator of «Life of St. David Garejeli» (10th century) relied on when writing his work, Bubakri was presented as a person of Monophysite confession. The text showed that the Monophysite was going to kill the holy monk and he changed his mind only after Bubakr and his son were cured of their illnesses by this monk. According to the authors of the article, as Monophysitism was presented in a negative context in the Bubakr episode, the creator of the new monument about St. David Garejeli did not mention the word «Armenian» at all. After the church split between them, they tried to repair the broken relationship, and presenting Monophysitism in a negative context would not contribute to the improvement of this relationship. Bubakr is presented as a positive person in the monument, it is shown that he showed strong faith in God and became a true Christian.